Phosphate-Containing Prescription Medications Contribute to the Daily Phosphate Intake in a Third of Hemodialysis Patients - Nelson, Seana M L; Sarabia, Samantha R S; Christilaw, Erin; Ward, Emilie C; Lynch, Stephanie K; Adams, Michael A; Holden, Rachel M (Journal of renal nutrition, 2017)
Hyperphosphatemia is associated with all-cause mortality in hemodialysis (HD) patients and is managed by restricting dietary phosphate. Many patients are unable to adhere to the recommended dietary phosphate limit. We sought to quantify the additional phosphate burden from prescription medication in a hemodialysis population. Cross-sectional study. Adult patients on hemodialysis at a single center. The Health Canada Drug Product Database was used to identify formulations of medications prescribed in an HD program that contain phosphate salts. The manufacturers of formulations containing a phosphate salt were contacted to request the phosphate content per tablet, and amounts were confirmed in select medications by the malachite green method. Prescription bottles of 101 HD patients were evaluated. Reported phosphate contents were used to determine patients' daily phosphate load from prescribed medications. A total 1,744 drug formulations of 124 different medications were reviewed. A total of 185 (11%) contained a phosphate salt. Central nervous system (CNS) and cardiovascular (CVS) medications accounted for 65% and 24% of phosphate-containing medications, respectively. Of HD patients, 30% were taking at least one medication that contained phosphate. The median phosphate burden from prescribed medications was 111 (67-168) mg per day. Knowledge about the phosphate content of commonly prescribed drugs within different classes should influence prescribing patterns. Particular consideration of which formulation of CVS and CNS drugs contain phosphate should be applied when prescribing. Phosphate-containing medications can meaningfully contribute to the daily phosphate load in HD patients; however, this burden will differ based on local dispensing patterns.